Filipinos and Indians as English Language Teachers in the Emirates: A Phenomenology - Henry E. Lemana II (International Journal of Qualitative Research, 2022)
Non-native English speakers, venturing abroad to work as English teachers, have drastically grown in number. In the United Arab Emirates, a country that regards English as a vital aspect of progress and sustainability and a home to more than 200 nationalities, Filipino and Indian teachers have found their platform to practice their profession, while facing the reality that such a country openly prefers to hire native speakers over non-native ones. Hence, this study was conducted to explore the lived experiences of 12 non-native English speakers (six Filipinos and six Indians) in the context of working as English language teachers in the UAE. Responses, collected through in-depth interviews, were analyzed to shed light on the overarching question. Findings revealed that informants came to the UAE to earn a bigger salary, grow personally and professionally, and enhance their communication skills. Furthermore, issues and challenges experienced by these teachers were clustered into personal matters (homesickness, new environment adjustments, and language barriers) and professional matters (preference for native speakers, curriculum adjustment, classroom environment, and teacher-parent connection). Data also unraveled the coping mechanisms of the informants: recalling motivations, building connections, utilizing various teaching approaches, and practicing cultural sensitivity. Finally, this study reflected the insights of the teachers, categorized in themes of unlimited learning, native vs. non-native speakers’ salary difference, uninterested learners, and the importance of understanding the work contract. Based on the findings, implications on administrative and pedagogical practices were explicated, leading to recommendations for future research on the phenomenon of teacher migration.